Penetapan Sita Eksekusi oleh Pengadilan Tanpa Didasari Diktum Putusan Akhir yang Mengabulkan Sita Jaminan (Analisis terhadap Perkara Nomor 332/ PDT.G/2016/PN.JKT.SEL) - Anita Afriana; Abdoel Harun Lamo (Departemen Hukum Perdata, 2020)
A civil dispute issue was raised by litigants to the court in order to obtain a ruling. As for the verdict has power the law remains, the content was ﬁ nal judgement that can be executed. The ﬁ nal decisions that have permanent legal force should be able to be implemented voluntarily or if not, then it can be done by force (execution). In practice, there is a case where the execution decision by the chair of the court is absent and is not based on a court rulling stating that a valid and valuable consifcation guarantee. This article discusses process Letter of Determination of Conﬁ scation of Execution without being based on a judge's decision that granted conﬁ scation of collateral in case No. 332/Pdt.G/2016/ PN.Jkt.Sel and the legal consequences of the party executed by the Execution Seizure determined by the head of court in case No. 332/Pdt.G/2016/PN.Jkt.Sel, when the decision has been legally binding it is still associated with the principle of legal certainty in the HIR. The research method used in this thesis is normative juridical which puts forward secondary data by completing primary data in the form of interviews with informants. With analytical analytics, secondary data and primary data are analyzed qualitatively. The results of this research indicate that the determination of the conﬁ scation of execution issued by the chairman of the Court in case No. 332/Pdt.G/2016/PN.Jkt.Sel is valid, if it is related to Article 227 HIR that a decision has permanent legal force, the winning party may submit a seizure of execution conﬁ scation that was never previously stipulated in the decision and the legal consequences against Determination of execution, namely the Defendant's assets must be conﬁ scated in accordance with the determination of the execution for the beneﬁ t of the Plaintiff for the sake of legal certainty as the party won.